Against modernist illusions: why we need more democratic and constructivist alternatives to debunking conspiracy theories. Issue 1 (2nd January 2021) - Harambam, Jaron
ABSTRACT: Various societal and academic actors argue that conspiracy theories should be debunked by insisting on the truthfulness of real "facts" provided by established epistemic institutions. But are academic scholars the appropriate actors to correct people's beliefs and is that the right and most productive thing to do? Drawing on years of ethnographic research experiences in the Dutch conspiracy milieu, I explain in this paper why debunking conspiracy theories is not  possible  (can scholars actually know the  real  truth?), not  professional  (is taking sides in truth wars what we should do?), and not  productive  (providing more "correct" information won't work as knowledge acceptance is not just a cognitive/epistemic issue). Instead of reinstalling the modernist legitimation narrative of science, I argue in this paper for an alternative that is both epistemologically stronger and sociologically more effective. Building from research and experiments with epistemic democracy in the field of science and technology studies, I propose to have "deliberative citizen knowledge platforms", instead of elite experts groups alone, asses the quality of public information. Such societally representative bodies should enjoy more legitimacy and epistemic diversity to better deal with conspiracy theories and the broader societal conflicts over truth and knowledge they represent.